How do you evaluate e^( ( pi)/2 i) - e^( ( 19 pi)/12 i)eπ2i−e19π12i using trigonometric functions?
1 Answer
I get this.
Interestingly enough, you can use Euler's formula, which states:
\mathbf(e^(ix) = isinx+cosx)eix=isinx+cosx
Thus, you can substitute
e^(i*pi"/"2) - e^(i*19pi"/"12)ei⋅π/2−ei⋅19π/12
= [isin(pi/2) + cos(pi/2)] - [isin((19pi)/12) + cos((19pi)/12)]=[isin(π2)+cos(π2)]−[isin(19π12)+cos(19π12)]
We know that
= color(green)([isin(90^@) + cos(90^@)] - [isin(285^@) + cos(285^@)])=[isin(90∘)+cos(90∘)]−[isin(285∘)+cos(285∘)]
Okay, so what is
sin(285^@) = sin(-75^@) = -sin(75^@) = -sin(30^@+45^@)sin(285∘)=sin(−75∘)=−sin(75∘)=−sin(30∘+45∘)
Using the addition identity
=> -[sin30^@cos45^@ + cos30^@sin45^@]⇒−[sin30∘cos45∘+cos30∘sin45∘]
= -(1/2*sqrt2/2 + sqrt3/2*sqrt2/2)=−(12⋅√22+√32⋅√22)
= (-sqrt2-sqrt6)/4 ~~ -0.9659=−√2−√64≈−0.9659
Then, consider
cos(285^@) = cos(-285^@) = cos(75^@) = cos(30^@+45^@)cos(285∘)=cos(−285∘)=cos(75∘)=cos(30∘+45∘)
Using the addition identity
=> cos30^@cos45^@ - sin30^@sin45^@⇒cos30∘cos45∘−sin30∘sin45∘
= sqrt3/2*sqrt2/2 - 1/2*sqrt2/2=√32⋅√22−12⋅√22
= (sqrt6 - sqrt2)/4 ~~ 0.2588=√6−√24≈0.2588
So overall, we have:
color(blue)(e^(i*pi"/"2) - e^(i*19pi"/"12))ei⋅π/2−ei⋅19π/12
= [icancel(sin(90^@)) + cancel(cos(90^@))^0] - [isin(285^@) + cos(285^@)]
= i - i[(-sqrt2-sqrt6)/4] - [(sqrt6 - sqrt2)/4]
= -(sqrt6 - sqrt2)/4 + (1 - (-sqrt2-sqrt6)/4)i
= color(blue)(-(sqrt6 - sqrt2)/4 + (1 + (sqrt2+sqrt6)/4)i)
~~ color(blue)(-0.2588 + 1.9659i)